Defect Engineering with Rational Dopants Modulation for High-Temperature Energy Harvesting in Lead-Free Piezoceramics - Kaibiao Xi; Jianzhe Guo; Mupeng Zheng; Mankang Zhu; Yudong Hou (Nano-Micro Letters)
Highlights The solution limit of manganese ion in BiFeO3–BaTiO3 (BF–BT) was determined by combining multiple advanced characterization methods. The defect engineering associated with fine doping can realize the co-modulation of polarization configuration, iron oxidation state and domain orientation. The BF–BT–0.2Mn piezoelectric energy harvester shows excellent power generation capacity at 250 °C, which is an important breakthrough for lead-free piezoelectric devices.